THE USE OF DEMONSTRATION TECHNIQUE TO IMPROVE WRITING SKILL OF THE ELEVENTH GRADE STUDENTS - Firdayani, Firdayani; Nadrun, Nadrun; Rofiqoh, Rofiqoh; Maf'ulah, Maf’ulah (e-Journal of ELTS (English Language Teaching Society), 2025)
The objective of this research is to prove whether the application of demonstration technique can improve writing skills of the eleventh-grade students of SMA Negeri 1 Witaponda or not. The population of this research is the eleventh-grade students of SMA Negeri1 Witaponda, the sample was XI IPS2 as experimental class and XI IPS3 as control class. The number of each sample was 21 students. The research applied quantitative method. The instruments of the data collection were pre-test and post-test. The finding showed that the experimental group's mean score on the post-test was 72 and the pretest was 56.6. Whereas the control group's mean score on the post-test is 45.7 and the pretest is 53.5. The results of data analysis revealed that the value of the t-counted (3.804) was higher than the value of the t-table (1.684) by applying a significant level of 0.05 with a degree of freedom (df). It means that the hypothesis is accepted. It indicates that there is a significant improvement. In addition, the implications of these findings can be concluded that the use of demonstration techniques was effective for teaching writing procedure texts because it can help practice their ideas and help teachers transfer material related to the lesson.